Cinema studies : the key concepts - Hayward, Susan, 1945-; Hayward, Susan, 1945- (London : Routledge, 2000)
150 key genres, movements, theories, and production termsare explained and analysed. Entries include auteur theory, black cinema, British new wave, feminist film theory, intertextuality, method acting, pornography, third world cinema and war films.
Earlier ed. has title: Key concepts in cinema studies.
Includes bibliographical references and index.
Keywords: Motion pictures -- Encyclopedias; Cinematography -- Encyclopedias